Knowledge, attitude, and practice of pesticide use among agricultural workers of Lamatar Village Development Committee, Lalitpur District: A cross-sectional study - Jyoti, Sabita; Lama, Prasanna; Yadav, Anika; Vaidya, Subhadra; Joshi, Sunil Kumar (International Journal of Occupational Safety and Health, 2023)
Introduction: In this fast-developing world, food production has also been changing, making people suffer from various health issues because of pesticide poisoning. Unsafe methods in handling pesticides, especially in middle and low-income countries like Nepal are still practiced, although the deleterious health effects either go unnoticed or are missed or are diagnosed late. Few of the older less costly pesticides remain for years in soil and water although few of them have been banned they are still available in many developing countries. The study aimed to assess knowledge, attitude, and practice regarding pesticide use among agricultural workers and farmers’ awareness of pesticide labels on pesticide bottles or packets. Methods: A cross-sectional study among 74 conveniently selected agricultural workers, who used or ever-used pesticides within the last six months was conducted in Lamatar Village Development Committee, Lalitpur District from January 2022 to February 2022. Ethical clearance was obtained from the Institutional Review Committee of Kathmandu Medical College. The questionnaire was adapted from literature about personal protective equipment with some modifications according to the local context. Data was collected through a face-to-face interview. Results: Among the total 74 respondents 49 (66.2%) were females and only 25 (33.8%) were males. Most of them had no formal education but could read and write. However, less than half 32 (43.2%) had adequate knowledge while the majority 49 (66.2%) had a negative attitude towards the use of pesticides. However, only 32 (43.2%) had good practice handling pesticides and its effect. Conclusion: This study showed low knowledge regarding pesticides, their health effects, and poor practice however, a negative attitude towards the use of pesticides. But pesticide is still widely used because of the demand for more earnings. So, we would recommend that there is a need for time-to-time regular community-based training regarding how to safely handle pesticides and the availability of less harmful fertilizers products at retailers or consultancies.